A Modified Global Management Controller for a Grid-connected PV System with Battery under Various Power Balance Modes - Diana Obaid; Ali Mahdi; Mohammed Alkafaji (Engineering and Technology Journal, 2023)
This work presents an Energy Management System (EMS) constructed on dissimilar power balance modes and dynamic grid power to activate a DC-link microgrid with a solar (PV-array) generator and battery storage. In addition, the option of requesting adjustable power from the grid to encounter load demand is also presented.  Based on the availability of solar sources, battery state, and grid power, energy management offers the appropriate references for all modes. Six power balance options are defined based on power supply, storage system, and grid mobility to match the load requirement. The aims are to reduce energy usage and upsurge the life of the storage device. The microgrid is controlled to maintain a consistent DC-link voltage and manage the battery current depending on the mode of operation. Using MATLAB\SIMULINK software, the anticipated energy management system, which is based on power balancing modes, is tested under various scenarios. The simulation results demonstrated that the microgrid operated admirably, with seamless switching between power balance modes.